Exosome-based intercellular communication in female reproductive microenvironments - Ranjbaran, Ali; Latifi, Zeinab; Nejabati, Hamid Reza; Abroon, Sina; Mihanfar, Aynaz; Sadigh, Aydin Raei; Fattahi, Amir; Nouri, Mohammad; Raffel, Nathalie (Journal of Cellular Physiology, 2019)
Different strategies are applied for cellular cross-talk and organization in multicellular organisms. Exosomes are a homogenous population of biological nanoparticles (30–100 nm), originated from multivesicular bodies. The exosomes (Exos) could regulate and affect both cellular physiology and pathophysiology in various organs, such as the female reproductive tract, by altering gene pathways and/or epigenetic programming. Besides, engineered Exos have the potential to be used as a novel drug and gene delivery tools. Here in this review, we discussed various aspects of exosome-based intercellular communication in female reproductive microenvironments. Furthermore, we addressed the findings and issues related to Exos in reproductive biology to give a better view of the involved molecular mechanisms. Moreover, clinical applications of the Exos and their isolation source/methods have been considered to throw some light on the progression of new biological, diagnostic, and therapeutic approaches in clinical embryology.
CRIS-Team Scopus Importer:2019-08-06
Keywords: cell communication; embryology; exosome; female reproduction